Low-Dose CT for Craniosynostosis: Preserving Diagnostic Benefit with Substantial Radiation Dose Reduction - Montoya, J.C.; Eckel, L.J.; DeLone, D.R.; Kotsenas, A.L.; Diehn, F.E.; Yu, L.; Bartley, A.C.; Carter, R.E.; McCollough, C.H.; Fletcher, J.G. (American Journal of Neuroradiology, 2017)
BACKGROUND AND PURPOSE: Given the positive impact of early intervention for craniosynostosis, CT is often performed for evaluation but radiation dosage remains a concern. We evaluated the potential for substantial radiation dose reduction in pediatric patients with suspected craniosynostosis.MATERIALS AND METHODS: CT projection data from pediatric patients undergoing head CT for suspected craniosynostosis were archived. Simulated lower-dose CT images corresponding to 25%, 10%, and 2% of the applied dose were created using a validated method. Three neuroradiologists independently interpreted images in a blinded, randomized fashion. All sutures were evaluated by using 3D volume-rendered images alone, and subsequently with 2D and 3D images together. Reference standards were defined by reader agreement by using routine dose and 2D and 3D images. Performance figures of merit were calculated based on reader response and confidence.RESULTS: Of 33 pediatric patients, 21 had craniosynostosis (39 positive sutures and 225 negative sutures). The mean volume CT dose index was 15.5 ± 2.3 mGy (range, 9.69–19.38 mGy) for the routine dose examination. Average figures of merit for multireader analysis ranged from 0.92 (95% CI, 0.90–0.95) at routine pediatric dose to 0.86 (95% CI, 0.79–0.94) at 2% dose using 3D images alone. Similarly, pooled reader figures of merit ranged from 0.91 (95% CI, 0.89–0.95) at routine pediatric dose to 0.85 (95% CI, 0.76–0.95) at 2% dose using 2D and 3D images together. At 25% and 10% dose, 95% CI of the difference in figures of merit from routine dose included 0, suggesting similar or noninferior performance.CONCLUSIONS: For pediatric head CT for evaluation of craniosynostosis, dose reductions of 75%–90% were possible without compromising observer performance.CTDIvolvolume CT dose indexFOMfigure of merit